2020
DOI: 10.31674/mjn.2020.v11i03.010
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Stress Level and Academic Procrastination Among New Nursing Students

Abstract: Student in the university will undergo complex transition process from high school student life to be university student. They must adapt with academic challenges that should be confronted during study such as assignments, time management, and academic evaluation. This causes students to get stress that lead them to postpone assignments which is called academic procrastination. This study aims to identify relationship between stress level and academic procrastination among new nursing students. Correlational c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…For instance, in the study conducted on a sample of 140 Chinese medical students ( Khalid et al, 2019 ), procrastination induced stress among students. Muliani et al (2020) also confirmed that there was a significant relationship between procrastination and stress. This finding is in total agreement with our study.…”
Section: Discussionsupporting
confidence: 59%
“…For instance, in the study conducted on a sample of 140 Chinese medical students ( Khalid et al, 2019 ), procrastination induced stress among students. Muliani et al (2020) also confirmed that there was a significant relationship between procrastination and stress. This finding is in total agreement with our study.…”
Section: Discussionsupporting
confidence: 59%
“…In this study, the Holmes and Rahe Stress Scale questionnaire was used as a screening questionnaire for sample selection to exclude medical students who were experiencing severe stress. Muliani, Imam, and Dendiawan stated that stress can cause procrastination (Muliani et al, 2020). This may explain why the sample of Mortazavi experienced higher academic procrastination than the research conducted at the Faculty of Medicine Mulawarman University.…”
Section: Tabel 3 Tendency To Procrastinatementioning
confidence: 88%
“…Psychological stress can reduce one's ability to remember, causes sadness, and procrastination events. 11 Procrastination and stress can affect each other. This cycle is difficult to break and can reduce the ability to do things effectively.…”
Section: Discussionmentioning
confidence: 99%